Capillary electrophoresis with laser-induced fluorescence detection used in metabolite profiling - Tseng, Hua-Ming (2009)
Novel and sensitive CE methods coupled with LIF and LINF detection using a series of separation modes have been developed for profiling organic metabolites containing amines and carbohydrates in mammalian and plant biofluids. In this study, metabolites containing an amine group were derivatized with 4-Fluoro-7-nitro- benzofurazan (NBD-F), separated by micellar electrokinetic chromatography (MEKC), and detected by argon-ion (488 nm) laser-induced fluorescence detection (LIF). Under the optimized conditions most of the amine-containing metabolites in human biofluids such as plasma, urine and saliva could be identified by reference to standard compounds and the concentrations measured were found to be in agreement with literature values.